Penerapan Ruang Fleksibel Terhadap Aktivitas Pengguna Pasar Tradisional Kemakmuran di Kabupaten Kotabaru - Indah Pradnya Haryanti; Wiliarto Wirasmoyo (RUAS, 2021)
Market is not supported by good facilities and further strengthens the stigma of traditional markets which are slum, crowded, and the smell becomes strong. This study aims to get rid of the bad image of traditional markets so that it attracts more visitors from various circles and optimizes the function of space in the market. The method used in this research is a rational approach and it is resolved with a flexible space approach applied to the choice of building structure, layout, design of the building, and furniture. The results of the implementation of this flexible space can accommodate all activities in the market according to the needs at certain times without disturbing other ongoing activities with a good zoning division in accordance with SNI Pasar Rakyat, so as to create a clean, neat, organized, and clean market. convenient according to user needs.